Subjective Evaluation of Defocus and Astigmatism Combinations Using Image Simulation in Presbyopes. Issue 1 (January 2021) - Vincent, Marc; Marin, Gildas; Legras, Richard
Abstract : SIGNIFICANCE: Image simulation is a useful and efficient tool to explore the impact of defocus and astigmatism combinations on visual acuity and image quality score when accommodation is taken into account. PURPOSE: The goal of this experiment was to determine if a simulation is able to predict visual acuity and image quality score (IQS) with defocus and astigmatism combinations in presbyopes. METHODS: We measured visual acuity and IQS in five defocus and astigmatism combinations in either real or simulated conditions. In real conditions, the subjects viewed a stimulus through an ophthalmic lens or a deformable mirror. In simulated conditions, subjects viewed images of the same stimulus with simulated blur. The amounts of defocus and astigmatism combinations of a progressive addition lens in near vision were generated through a static correction of the subject's aberrations. We simulated three levels of accommodation: subject could not accommodate (FOC0), subject could accommodate to the less hyperopic focal point (FOC1), or subject could accommodate to the circle of least confusion (FOC2). RESULTS: Visual acuity or IQS did not differ between mirror and progressive addition lens conditions. Visual acuity measured in real blur conditions differed significantly from that in FOC0 simulated blur condition but were similar to that in FOC1 and FOC2 simulated blur conditions. Image quality score obtained in real conditions were between scores measured with the FOC0 and FOC1 simulated conditions, suggesting that the subjects were able to produce a low level of accommodation. CONCLUSIONS: Accommodation may play a role when comparing optical and simulated defocus and astigmatism combinations. Presbyopic subjects are able to produce a low level of accommodation that may counterbalance a part of the deleterious effect of the astigmatism on image quality. Simulation remains a useful tool if the correct accommodation state is taken into account.